Social, Economic and Health Status of Aging People in Surrounding Areas of Kathmandu - Khanal, Kashi Nath (Interdisciplinary Journal of Management and Social Sciences, 2023)
Aging is most recent phenomenon of the world population- none of the countries in the world is excluded from this spectacle. The aging of population in Nepal is growing in acceleration comparing to other segments of human population. As population transition shifts to the aging, it brings changes in social pattern, social structure and social relations. This article brings into discussion about various aspects of socio-economic status of aging people in Nepal, based on outer circle of Kathmandu city. Socio-economic status of aging people is more or less associated with the socio-economic status of family itself and, of course, of a country. Aging is not only associated with age, but also intermingled with various socio-economic factors of different arena of a society. Researches on concerned field has explored that increase of aging population pose challenges to family, society and nation. Moreover, aging people are at the risk because of individual, behavioral and surrounding factors that include level of education, past and present occupation, level of income, youth migration, accessible infrastructure, provisions of social security and many more that is discussed in the following lines. Such and other factors contribute for health risks in aging. In this scenario, this paper accounts socio-economic status of aging people in Nepal in the present context.